Excessive and pathological Internet use – Risk-behavior or psychopathology?. (December 2021) - Kaess, Michael; Klar, Johanna; Kindler, Jochen; Parzer, Peter; Brunner, Romuald; Carli, Vladimir; Sarchiapone, Marco; Hoven, Christina W.; Apter, Alan; Balazs, Judit; Barzilay, Shira; Bobes, Julio; et al.
Highlights: Pathological Internet use fits to a latent "psychopathology factor". Excessive Internet use fits to a latent "risk behavior" factor. A dimension ranging from normal via risky to pathological Internet use is likely. A dimensional approach could be applied to guide prevention and intervention. Abstract: Pathological Internet use (but only with respect to gaming) is classified as mental disorder in the ICD-11. However, there is a large group of adolescents showing excessive Internet use, which may rather be considered adolescent risk-behavior. The aim was to test whether pathological and excessive Internet use should be considered as "psychopathology" or "risk-behavior". A representative, cross-sectional sample of 11.110 students from 10 European Union countries was analyzed. Structural equation models, including the factors "risk-behavior" and "psychopathology" and the variables excessive and pathological Internet use, were tested against each other. "Risk-behavior" was operationalized by several risk-behaviors (e.g. drug abuse, truancy, etc). "Psychopathology" included measures of several mental disorders (e.g. depression, hyperactivity, etc). Excessive Internet use was assessed as the duration and frequency of Internet use. Pathological Internet use was assessed with the Young Diagnostic Questionnaire (i.e., presence of addiction criteria). Excessive Internet use loaded on "risk-behavior" (λ = 0.484, p < .001) and on "psychopathology" (λ = 0.071, p < .007). Pathological Internet use loaded on "risk-behavior" (λ = 0.333, p < .001) and on "psychopathology" (λ = 0.852, p < .001). Chi-square tests determined that the loadings of excessive Internet use (χ 2 (1) = 81.98, p < .001) were significantly stronger on "risk-behavior" than "psychopathology". Vice versa, pathological Internet use loaded significantly stronger on "psychopathology" (χ 2 (1) = 107.10, p < .001). The results indicate that pathological Internet use should rather be considered as psychopathology. Excessive Internet use on the other hand, should be classified as adolescent risk-behavior.